Effect of Gamma Radiation on Some Physical Properties of Polyvinyl Alcohol Dissolve in Dimethyl Sulfoxide (Journal of the College of Basic Education, 2022)
In this investigation the Rheological properties of Polyvinyl Alchohol (PVA) dissolves in Dimethyl Sulfoxide with different concentrations has been investigated before and after irradiation by gamma-ray Coblat (Co60) with different doses rate 50, 100 and 150 (Rad/min) for minutes. These properties are Density, shear viscosity, relative viscosity, specific viscosity and reduced viscosity have been measured. Also the average viscosity molecular weight and effective molecular radius have been calculated.